OPTIMALISASI PENERIMAAN PBB-P2 (PAJAK BUMI DAN BANGUNAN) MELALUI VERIFIKASI DAN VALIDASI DALAM MENINGKATKAN PAD (PENDAPATAN ASLI DAERAH) PADA BADAN PENDAPATAN DAERAH KABUPATEN SIKKA - Maria Yuliana Mi; Andreas Rengga; Elisabet Luju (Jurnal Projemen UNIPA, 2026)
Land and Building Tax for Rural and Urban Areas (PBB-P2) is one of the sources of Regional Original Revenue that has a strategic role in supporting regional development financing. However, the optimization of PBB-P2 revenue still faced various problems, especially related to the inaccuracy of tax object and subject data. This study aimed to analyze the optimization of PBB-P2 revenue through the implementation of verification and validation in increasing PAD at the regional Revenue Agency (BAPENDA) of Sikka Regency. The research method used was a qualitative approach with data collection techniques through interviews, observations, and documentation. The results showed that the implementation of verification and validation of PBB-P2 data was able to improve the accuracy of the tax database, refine the determination of the Tax Object Sales Value, and reduce data discrepancies between the system and field conditions. These efforts had a positive impact on increasing the realization of PBB-P2 revenue and its contribution to PAD of Sikka Regency. Nevertheless, the implementation of verification and validation still faced several obstacles, such as limited human resources, suboptimal utilization of information technology, and low awareness among some taxpayers. Therefore, strengthening the data collection system, increasing the capacity of apparatus, and enhancing inter-agency synergy were required to optimize PBB-P2 revenue sustainably.